Beyond the polis (Bruxelles)
302 sayfa
Keywords: “This peer reviewed volume presents the proceedings of the international conference that took place in Brussels in 2015 and the sequel to the publication of the research that resulted from a three-year joint project between the University of Oxford and the Université libre de Bruxelles (ULB). The volume offers complementary approaches, both thematic and geographic, to the study of Early Greek ritual practices and expands into other areas, contexts, and materials the research undertaken in the volume Constructing Social Identities in Early Iron Age and Archaic Greece edited by Athena Tsingarida and Irene Lemos in 2017. The volume includes papers on theoretical approaches to the study of rituals, case studies from a number of regions and sites, and finally papers on the contribution of bio-archaeological research to our understanding of ritual practices in ancient Greece.” --